Quantitative Real-Time PCR for Determination of Microcystin Synthetase E Copy Numbers for Microcystis and Anabaena in Lakes - Vaitomaa, Jaana (American Society for Microbiology, 2003)
Cyanobacterial mass occurrences in freshwater lakes are generally formed by Anabaena, Microcystis, and Planktothrix, which may produce cyclic heptapeptide hepatotoxins, microcystins. Thus far, identification of the most potent microcystin producer in a lake has not been possible due to a lack of quantitative methods. The aim of this study was to identify the microcystin-producing genera and to determine the copy numbers of microcystin synthetase gene E (mcyE) in Lake Tuusulanjärvi and Lake Hiidenvesi in Finland by quantitative real-time PCR. The microcystin concentrations and cyanobacterial cell densities of these lakes were also determined. The microcystin concentrations correlated positively with the sum of Microcystis and Anabaena mcyE copy numbers from both Lake Tuusulanjärvi and Lake Hiidenvesi, indicating that mcyE gene copy numbers can be used as surrogates for hepatotoxic Microcystis and Anabaena. The main microcystin producer in Lake Tuusulanjärvi was Microcystis spp., since average Microcystis mcyE copy numbers were >30 times more abundant than those of Anabaena. Lake Hiidenvesi seemed to contain both nontoxic and toxic Anabaena as well as toxic Microcystis strains. Identifying the most potent microcystin producer in a lake could be valuable for designing lake restoration strategies, among other uses.